Hydrogen-fueled CO2 reduction using oxygen-tolerant oxidoreductases - Cha, Jaehyun; Bak, Hyeonseon; Kwon, Inchan (Frontiers in Bioengineering and Biotechnology, 2023)
Hydrogen gas obtained from cheap or sustainable sources has been investigated as an alternative to fossil fuels. By using hydrogenase (H2ase) and formate dehydrogenase (FDH), H2 and CO2 gases can be converted to formate, which can be conveniently stored and transported. However, developing an enzymatic process that converts H2 and CO2 obtained from cheap sources into formate is challenging because even a very small amount of O2 included in the cheap sources damages most H2ases and FDHs. In order to overcome this limitation, we investigated a pair of oxygen-tolerant H2ase and FDH. We achieved the cascade reaction between H2ase from Ralstonia eutropha H16 (ReSH) and FDH from Rhodobacter capsulatus (RcFDH) to convert H2 and CO2 to formate using in situ regeneration of NAD+/NADH in the presence of O2.